ASSESSMENT OF CLINICAL FEATURES IN PATIENTS WITH DEPRESSION - Kshirsagar, Sharad.V.; Mangot, Ajish; Tembe, Dr. Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Depression is a commonly occurring mental health ailment. The present study was conducted to assess clinical features in patients with depression.This study was conducted on 252 cases of major depressive disorder (MDD). Education status, family history, employment and marital status was recorded. All were subjected to the 30-item Inventory of Depressive Symptomatology–Clinician-Rated (IDS-C30) scale. Out of 252 patients, males were 82 and females were 170. We found that 97 had education upto high school, 110 upto secondary and 45 upto higher, 65 were married, 95 unmarried, 40 divorced and 52 were widow. 82 had income between 10000- 20000, 112 had between 20000-50000 and 58 had >50000, 187 were employed and 65 were unemployed, 158 had family history of depression. IDS-C30 Items showed onset insomnia in 110, middle insomnia in 67, early morning insomnia in 30, mood (sad) in 45, mood (irritable) in 59, mood (anxious) in 120, mood reactivity impaired in 132, mood variation by day of time in 45, distinct mood quality in 70, decrease appetite in 60, increase appetite in 89, weight decrease in 95, weight increase in 56. Authors found that depression is a major psychiatric disorder more prevalent in females as compared to males. Common clinical features were decreased appetite, weight loss, mood alteration, suicidal attempt.